2012
DOI: 10.4067/s0717-95022012000100028
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Skull Size and Brain Volume, with Age, Weight, Height and Body Mass Index of Arak Medical Sciences Students

Abstract: SUMMARY:Anthropometric indices that are indicators of nutrition status in children and adults can be affected by racial and geographic factors. The aim of present study was to investigate the relation of skull size and brain volume of Arak University of Medical Sciences students with their age, weight, height and body mass index. The present study was a cross-sectional study on 18-26 years old students of Arak University of Medical Sciences (150 female and 136 male) in 2009-2010 educational year. Sampling meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
7
0
2
Order By: Relevance
“…Since the temporalis muscle travels a longer distance on the skull than the masseter and lateral pterygoid muscles, its size is more dependent on the head volume. Similarly, an antecedent anthropometric study identified a high correlation between brain volume and BMI-partially supporting this issue 36 .…”
Section: Intra-rater Icc (95% Ci)mentioning
confidence: 69%
“…Since the temporalis muscle travels a longer distance on the skull than the masseter and lateral pterygoid muscles, its size is more dependent on the head volume. Similarly, an antecedent anthropometric study identified a high correlation between brain volume and BMI-partially supporting this issue 36 .…”
Section: Intra-rater Icc (95% Ci)mentioning
confidence: 69%
“…Can be due to the difference in head form in races and people in different geographical areas, it can be said that inheritance is the head cause of changes in the shape of the head and the environmental factors after that have the greatest impact. 17 It should be noted that the reaction to a specific environment indicates the response of the genotype of that population to the environment. 18 This study shows that the head are more common in children of Kabul city is broad, but unfortunately, for such a study to determine the head index has not been made in Afghanistan and there is no further information on the head index of different ages and ethnicities.…”
Section: Discussionmentioning
confidence: 99%
“…yang dilakukan pada murid usia 18-26 tahun dengan mengukur tinggi badan, berat badan, panjang kepala, lebar kepala dan lingkar kepala. 13 Hasil penelitian menunjukkan korelasi positif antara volume otak dan pengukuran antropometri termasuk tinggi, berat, usia dan indeks massa tubuh. Korelasi tertinggi ditemukan pada volume otak dan indeks massa tubuh.…”
Section: Pendahuluanunclassified
“…Hasil penelitian tersebut terlihat bahwa ukuran lingkar kepala menurun seiring dengan meningkatnya ukuran tinggi badan. 13 Pada penelitian yang dilakukan Geraedts dkk. adanya korelasi antara lingkar kepala terhadap berat badan dan tinggi badan.…”
Section: Pendahuluanunclassified